A DIFFERENT APPROACH TOWARDS SOCIAL MEDIA: CHINESE YOUNG CONSUMERS BEHAVIOUR INSIGHTS - MODREANU ANDRA; TOMA SORIN-GEORGE; GRĂDINARU CĂTĂLIN (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2023)
Social media has changed the dynamics of the social and business environment by impacting the thinking, expressions, beliefs, behaviour, and motivation level of individuals. Young consumers spend more and more time on social media, becoming an ideal platform for companies to promote products and services. The purpose of this research is to gain a better understanding of social media in the Chinese context and to examine the marketing potential of these platforms among young chinese individuals, considering their online behaviour. The results show that Chinese aim to maintain a specific social class and reputation in their online communities and most of their purchasing decisions are influenced by peer pressure.